Effects of H2S injection on the CO2-brine-sandstone interaction under 21 MPa and 70 °C. Issue 1 (15th May 2016) - Li, Chenyang; Zhang, Fengjun; Lyu, Cong; Hao, Jie; Song, Jianbin; Zhang, Shengyu
Abstract: In this study, laboratory experiments were conducted to investigate the influences of H2 S injection on the capacity of CO2 's solubility trapping and mineral trapping. Results demonstrated that the preferential dissolution of H2 S gas into brine (compared with pure CO2 ) resulted in the decrease of pH, consequently inhibiting the CO2 's solubility trappings to some extent. Then, the lower pH droved more severe corrosion of primary minerals, favored more secondary mineral to be formed. In addition, the discovery of pyrite demonstrated that H2 S could precipitate by the formation of sulfide mineral trapping. As the secondary carbon sink minerals, ankerite and dawsonite were observed in the pure CO2 -brine-sandstone interaction. However, there were no secondary carbonates found through the SEM images and EDS analyses, implied that the injection of H2 S probably may partially inhibit the precipitation of Fe-bearing carbonate minerals such as ankerite in the CO2 -H2 S-brine-sandstone interaction in this short term experiments. Highlights: H2 S injection gas would drove more severe corrosion of primary minerals. H2 S injection would inhibit the CO2 's solubility trappings to some extent. The precipitation of pyrite may inhibit the precipitation of Fe-bearing carbonate minerals.